Thinking tomorrow today: planning for uncertainty and building organisational culture that can walk the talk / Sadeeq Garba Abubakar - Abubakar, Sadeeq Garba (Universiti Teknologi MARA, Shah Alam, 2019)
Thinking tomorrow, today is about generating and manipulating ideas proactively and progressively. The critical issue is about expanding the scope of understanding all the facets of the organisational activities, and maintaining same approach and strategy through the future in a sustained manner. Manager’s ability should be screened on the basis of their pro-activeness and innovativeness in the management of thoughts that would foster the organisational advancement and effectiveness. This study is based on a case study design using secondary sources of data from a tertiary educational institution through an in-depth study and analysis of its organisational culture. Many of the early studies of this occurrence identified strong support for the idea that organisational culture and performance were indistinguishably linked. Recommendations given include the use of competitive and time effective management process to review, update, integrate, implement visions, decisions, and plans for tomorrow, whether in expansionary or recessionary times.